Biomechanical Evaluation of Y-Strut Dual Headless Compression Screws Versus Single Intramedullary Screw Fixation in Proximal Phalanx Fractures - Lie, Samuel; Massard-Combe, Philippe; Farshidfar, Sara Sadat; Baba, Mohammed (The Journal of hand surgery (American ed.), 2025)
To investigate whether a Y-strut configuration of dual headless compression screws provides greater force to failure when compared with a single intramedullary screw (IMS) in the fixation of proximal phalanx fractures. A biomechanical cadaveric study comparing Y-strut fixation with a single IMS in proximal phalanx fractures was performed. Sixteen proximal phalanges were dissected out from 4 hands of 2 fresh frozen cadavers and a fracture was created with a surgical saw. Specimens were divided into 2 groups and underwent fixation. Phalanges were mounted to a 3-point bending jig and tested to determine stiffness and load to failure. The specimens in the single screw group demonstrated higher load to failure than in the dual screw group (250.8 N vs 197.0 N). Stiffness also generally was higher although this result was not statistically significant. Fixation of simple proximal phalanx fractures with a single 3.0 mm IMS had a greater force to failure than with dual 2.2 mm screws in a Y-strut configuration, although there was no significant difference in stiffness. Fixation of a simple base of proximal phalanx fracture with dual 2.2 mm screws in Y-strut configuration results in a lower load to failure than with a single 3.0 mm screw. The shorter length of the second screw in this configuration may contribute to this result. Further investigation is required to investigate other configurations of dual screws.